2018
DOI: 10.1177/1945892418768584
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Endoscopic Sphenopalatine Artery Ligation Compared With Embolization for Intractable Epistaxis: A Long-term Analysis

Abstract: Background Transnasal endoscopic sphenopalatine artery ligation (TESPAL) and selective embolization both provide excellent treatment success rate in the management of intractable epistaxis. Few long-term studies comparing these approaches have been previously published. Recommendations often present these techniques as alternatives, but there is no clear consensus. Objective The purpose of this study was to evaluate and compare the clinical efficacy of sphenopalatine artery ligation versus embolization to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…e result was consistent with the results reported by McDermott et al [14] that CC for CIC was superior to vaginal progesterone in increasing the survival rate of newborns. It suggested that the optimal time to perform CC was in 14-18 weeks of gestational age [15]. Among the patients under investigation, in the observation group, 40 patients in group A were treated with CC before 17 weeks, 36 patients were successfully treated with a success rate of 89.6%, and 4 patients failed with a failure rate of 10.4%; in group B, 27 patients were treated with CC after 17 weeks, 19 patients were successfully treated with a success rate of 70.4%, and 8 patients failed with a failure rate of 29.6%.…”
Section: Discussionmentioning
confidence: 99%
“…e result was consistent with the results reported by McDermott et al [14] that CC for CIC was superior to vaginal progesterone in increasing the survival rate of newborns. It suggested that the optimal time to perform CC was in 14-18 weeks of gestational age [15]. Among the patients under investigation, in the observation group, 40 patients in group A were treated with CC before 17 weeks, 36 patients were successfully treated with a success rate of 89.6%, and 4 patients failed with a failure rate of 10.4%; in group B, 27 patients were treated with CC after 17 weeks, 19 patients were successfully treated with a success rate of 70.4%, and 8 patients failed with a failure rate of 29.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Se persistir hemorragia após trauma facial a intervenção precoce com métodos de imagem como a tomografia computadorizada e angiografia é recomendada, para o estudo de uma possível embolização vascular (Lee et al, 2009;Bonnecaze et al 2018;Chun et al, 2019). Nesse relato, a angiografia não foi realizada imediatamente, porque os tamponamentos nasais foram eficazes para cessar o sangramento no momento inicial.…”
Section: Discussionunclassified
“…The ligation reduces the discomfort, cost and potential medical morbidity compared to nasal packing. 11,12,13,14,15,16 This procedure was first described by Prades J. 17 Endoscopic SPA ligation was first described by Budrovich and saetti in 1992.…”
Section: Discussionmentioning
confidence: 99%